2021
DOI: 10.3390/biomedicines9080953
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve Prognostication in Acute Myeloid Leukemia with CBFB-MYH11 Fusion Transcript: Focus on the Role of Molecular Measurable Residual Disease (MRD) Monitoring

Abstract: Acute myeloid leukemia (AML) carrying inv(16)/t(16;16), resulting in fusion transcript CBFB-MYH11, belongs to the favorable-risk category. However, even if most patients obtain morphological complete remission after induction, approximately 30% of cases eventually relapse. While well-established clinical features and concomitant cytogenetic/molecular lesions have been recognized to be relevant to predict prognosis at disease onset, the independent prognostic impact of measurable residual disease (MRD) monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
(226 reference statements)
0
3
0
Order By: Relevance
“…Considering the CR rates of up to 93%, the induction mortality risk of 5% and approx. 25% of inv(16)-mut AML patients presenting with hyperleukocytosis [ 33 ], and assuming that all induction deaths happen in patients with hyperleukocytosis, the maximum early mortality is approx. 20% in patients with hyperleukocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the CR rates of up to 93%, the induction mortality risk of 5% and approx. 25% of inv(16)-mut AML patients presenting with hyperleukocytosis [ 33 ], and assuming that all induction deaths happen in patients with hyperleukocytosis, the maximum early mortality is approx. 20% in patients with hyperleukocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that measurable residual disease (MRD) monitoring during treatment is a powerful tool for evaluating therapy responses, predicting clinical outcomes, and providing treatment guidance 2–5 . Fusion transcript levels detected using the real‐time quantitative reverse transcriptase‐polymerase chain reaction (RQ‐PCR) method have been recognized as the most useful means for MRD monitoring and are applied in clinical settings for AML 3,6,7 . Moreover, with the development of next‐generation sequencing (NGS) and digital polymerase chain reaction (dPCR) techniques, gene mutation detection is being increasingly applied for MRD monitoring 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…2-5 Fusion transcript levels detected using the real-time quantitative reverse transcriptase-polymerase chain reaction (RQ-PCR) method have been recognized as the most useful means for MRD monitoring and are applied in clinical settings for AML. 3,6,7 Moreover,…”
mentioning
confidence: 99%